The Role of Decision Making for Family Activities by Industrial Labour of Women Migrant Based on Their Migration Characteristics - Susilongtyas, Dewi; Handayani, Tuty; Rahatiningtyas, Nurul Sri; Kusuma, Sigit Candra Winata; Lestari, Della Ayu (Forum Geografi, 2020)
The presence of women migrants in urban industrial workers proved that women's movement exists. This migration process not only indicates that women are actively involved in economic activity, but also influences the decision-making on important activities within the family and society. This study aims to determine the relationship between mobility patterns and its contribution to economic and decision-making in the family through the survey as research methods. The data were analysed by descriptive analysis, statistics approach, and correlation maps. For the independence test in the bivariate table, we used the chi square method, and to display the distribution of two variables simultaneously, a cross-tabulation was used. After that, to assess whether there is a relationship between the two variables, the table of independence was used. Our study shows that decision-making became an indicator of strengthening the role of women with a pattern of circular migration, which has a relationship on economic contribution. However, the behavior of women who perform the spatial migration in strengthening roles in families is not always relevant with the strengthening role of the economy. A strong role is only demonstrated by industrial migrant workers working on a circular migration pattern.